2009
DOI: 10.1112/s0010437x09004370
|View full text |Cite
|
Sign up to set email alerts
|

Smoothable del Pezzo surfaces with quotient singularities

Abstract: We classify del Pezzo surfaces with quotient singularities and Picard rank one which admit a Q-Gorenstein smoothing. These surfaces arise as singular fibres of del Pezzo fibrations in the 3-fold minimal model program and also in moduli problems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 16 publications
4
100
0
Order By: Relevance
“…Our main result characterises mutations between triangles; thus we characterise certain deformations, over P 1 , with fibers given by fake weighted projective planes. We recover and generalise certain results of Hacking and Prokhorov [HP10,Theorem 4.1] connecting the fake weighted projective planes with T -singularities to solutions of Markov-type equations. We prove the following: Proposition 1.1.…”
Section: Introductionsupporting
confidence: 77%
“…Our main result characterises mutations between triangles; thus we characterise certain deformations, over P 1 , with fibers given by fake weighted projective planes. We recover and generalise certain results of Hacking and Prokhorov [HP10,Theorem 4.1] connecting the fake weighted projective planes with T -singularities to solutions of Markov-type equations. We prove the following: Proposition 1.1.…”
Section: Introductionsupporting
confidence: 77%
“…In Sect. 6.3, we point out that the Markov type I equations have appeared before, in relation to 3-blocks exceptional collections in the del Pezzo surfaces [20] and Q-Gorenstein smoothing of weighted projective spaces to del Pezzo surfaces [16]. We ask if there is a correspondence between ATBDs, 3-blocks exceptional collections and Q-Gorenstein degenerations of a given del Pezzo surface (see Questions 6.2, 6.3).…”
Section: To Mutually Different Hamiltonian Isotopy Classesmentioning
confidence: 94%
“…In [16,Theorem 1.2], it is shown that the weighted projective planes that admit a Q-Gorenstein smoothing are precisely the ones given by the limit orbifolds of the ATBDs obtained by total mutation of the ones in Fig. 1.…”
Section: Question 62 Suppose We Have An Atbd With Node Typementioning
confidence: 99%
“…Here n(l) is the total number of LDP-polygons, m(l) is the number of LDPtriangles (i.e. rank one toric log del Pezzo surfaces), n T (l) is the number of LDP-polygons with T-singularities [20], and m T (l) is the number of LDPtriangles with T-singularities. For fixed index l, it is possible to classify all LDP-polygons [27].…”
Section: Fano Polygonsmentioning
confidence: 99%